SPECIFICS OF FUNCTIONING OF PERSONAL NAMES IN MODERN GREAT BRITAIN - Паладьєва, Алла (Modern engineering and innovative technologies, 2022)
The article outlines the specifics of the functioning of personal names in the light of the representation of an individual’s belonging to the community on national, religious and other features. It has been pointed out that the name is the bearer of a na